Educational technology and teacher training: challenges and solutions - Ahmed Mohamed, Ismaiel Hassanein (2012)
The twenty-first century witnessed tremendous progress in the field of information and communication technologies, education technologies, globalization, and modernization, in which the rich countries equip schools, colleges, institutes and universities with educational technologies which include computer labs, intranet (LAN &WAN), internet (the Web) & Wireless, projector, (LCD), multimedia, mobiles and digital media. Teacher are also trained how to use such educational technologies. On the contrary, the developing and poor countries, which make the majority of the world population, are still lagging far behind the rich countries in terms of those mentioned facilities in their schools. The majority of school teachers, colleges and university lectures are still “technology illiterate” and they have minimal basic knowledge about using technological devices and media. They are still using traditional instructional materials like the blackboard or green board with chalks. Hence, the contemporary educational settings need highly trained, multi-skilled and technologies literate teachers in order to carry out their mission professionally and effectively, and to face the growing challenges in the field of education. In line with the education demands, this paper aims to highlight the kind of teachers who are capable, dynamic and well equipped to work in schools ins such conditions. This paper also addresses the question of how the International Islamic University Malaysia can help to train and produce such teachers who can carry out their responsibilities locally and internationally. These teachers need to process versatility to ensure students are still educated to be ready for the ICT-based workplace when they leave school.